Soybean Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R. (My University, 2005)
This publication contains information for a projected budged reflecting expected income and cost based on soybean production practices in western Kansas.
MF2366_2005_10
Keywords: MF2366; Economics; Crops; MF